1999
DOI: 10.1046/j.1365-2036.1999.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Review article: current status of gastrointestinal carcinoids

Abstract: Carcinoid tumours are enigmatic, slow growing malignancies which occur most frequently (74%) in the gastrointestinal tract. In recent years, it has become apparent that the term `carcinoid' represents a wide spectrum of different neoplasms originating from a variety of different neuroendocrine cell types. Carcinoid lesions are usually identified histologically by their affinity for silver salts, by general neuroendocrine markers, or more specifically by immunocytochemistry using antibodies against their specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
75
1
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 90 publications
6
75
1
3
Order By: Relevance
“…The NETs occur 6.5-8.4 times more frequently in ileum than in duodenum and jejunum [13]. Even though primary tumour was only 2.5 cm, it had already metastasized to the liver and this is in accordance to studies conducted by Kaltsas et al [14].…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The NETs occur 6.5-8.4 times more frequently in ileum than in duodenum and jejunum [13]. Even though primary tumour was only 2.5 cm, it had already metastasized to the liver and this is in accordance to studies conducted by Kaltsas et al [14].…”
Section: Discussionsupporting
confidence: 79%
“…This patient had regional lymph node metastasis at time of diagnosis According to Modlin et al [2] colonic carcinoids are large tumors and commonly present with liver metastasis. Lauffer et al [13] indicated that colonic carcinoids had a female predominance with average age of 70 at the time of diagnosis, but in the present series all of the cases were men.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Table 3 summarizes the frequency of carcinoid at different sites (most occurring in the gut at 67.5%, then the lung at 25.3%), with the associated 5-year survivals. Predisposition to metastatic spread depends on location and size (Lauffer et al 1999, Modlin et al 2003.…”
Section: Carcinoidmentioning
confidence: 99%
“…1 2 The majority of cases have metastases at the time of diagnosis 3 and surgical cure is frequently not possible. Variation in their clinical behaviour and several potential treatment options make predicting prognosis desirable.…”
mentioning
confidence: 99%